ANALISIS PERBANDINGAN BIAYA DAN HARGA PADA RUMAH MAKAN KHAS MELAYU DAN RUMAH MAKAN PADANG DI KOTA PEKANBARU - Utami Nurhidayati; Jahrizal Jahrizal; Hamidi Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the cause of the high price of food in a typical Malay restaurant in Pekanbaru City and to find out the price competition with other regional restaurants, namely Padang restaurants.The sample in this study were Malay and Padang restaurant entrepreneurs in Pekanbaru City, which amounted to 10 restaurant units. Types of data include primary data and secondary data. Data collection techniques include questionnaires, interviews, and documentation. The researcher's data analysis technique used descriptive and quantitative descriptive.Based on the results of the study, it can be concluded that the total costs incurred per year by restaurants are 3:1 for Malay restaurants. The biggest cost incurred by restaurants, especially Malay restaurants, is for the purpose of providing raw materials for production. Based on the results of the research, the cause of the relatively high cost of cooking in typical Malay restaurants is the difficulty of obtaining the main raw materials in the production process. The selling price of products in typical Malay restaurants ranges from Rp. 16,000 – Rp. 200,000/portion, while the selling price of products at Padang restaurants ranges from Rp. 10,000 – Rp. 25,000/portion. The pricing strategy used by typical Malay restaurants is Skim the cream pricing or skimming pricing, which is the setting of the highest price to cover the costs incurred, development and promotion. While the price strategy used by Padang restaurants is Penetration Pricing, which means setting the lowest possible price with the aim of achieving the maximum sales volume in a relatively short time.Keywords: Restaurant Industries, Cost, Price